Mirabegron in the Management of Overactive Bladder Syndrome in Ghazi Al-Hariri Hospital - Razaq, Hiba H.; Ismail, Mohammed B.; Abdelrhman, Mohamed E. (Journal of the Faculty of Medicine Baghdad, 2025)
Background: An individual’s quality of life is adversely affected by overactive bladder (OAB) symptoms. The key element that characterizes OAB is urgency which together with nocturia and urge urinary incontinence, are considered the most irksome symptoms. The side effects of the anticholinergic medication have caused a significant number of patients to discontinue their treatment. More recently, there has been research conducted on the potential correlation between an anticholinergic burden and the development of dementia. The detrusor muscle has been demonstrated to relax as a result of the activation of β3 adrenoceptors, which in turn facilitated the development of the first β3 adrenoceptor agonist. Mirabegron is the initial medication in this category to receive approval for the treatment of an overactive bladder.Objectives: To explore the effect of mirabegron on bladder capacity in patients with OAB.Methods: A case series study was performed on 40 patients diagnosed with OAB from October 2023 to March 2024 in the Medical City Complex (Ghazi AL-Hariri Hospital) Urology Outpatient Clinic. These patients took a single dose of mirabegron 50 mg per day for four months and were assessed for the effect of this drug on the bladder capacity measurement, in milliliters, measured by ultrasound.Result: Following treatment with mirabegron, a statistically significant increase in bladder capacity was found from the baseline level after two and four months.Conclusion: Mirabegron is an effective drug for the treatment of OAB, as it increases bladder capacity.